Thymosin β4 protects C57BL/6 mice from bleomycin‐induced damage in the lung. (16th January 2013) - Conte, Enrico; Genovese, Tiziana; Gili, Elisa; Esposito, Emanuela; Iemmolo, Maria; Fruciano, Mary; Fagone, Evelina; Pistorio, Maria P.; Crimi, Nunzio; Cuzzocrea, Salvatore; Vancheri, Carlo
Abstract Background Thymosin β4 (Tβ4) was recently found at high concentration in the bronchoalveolar lavage fluid (BALF) of scleroderma patients with lung involvement. It has been hypothesized that Tβ4 may exert a cyto‐protective effect during lung injury because lower Tβ4 levels were associated with interstitial lung disease progression. Moreover, Tβ4 treatment prevented profibrotic gene expression in cardiac cells in vitro and in vivo. Materials and methods In this study, we explored a putative Tβ4 protective role in lung damage by utilizing a well‐known in vivo model of lung fibrosis. C57BL/6 mice were treated with bleomycin (BLEO, 1 mg/kg) in the absence or presence of Tβ4 (6 mg/kg delivered intraperitoneally on the day of BLEO treatment and for two additional doses). After sacrifice 1 week later, measurement of fluid and collagen content in the lung, BALF analysis, myeloperoxidase (MPO) activity assay, lung histology and IHC were performed. Results Compared with BLEO‐treated mice, BLEO‐treated mice who received Tβ4 did not lose as much weight and had a higher survival rate. Moreover, BLEO‐induced inflammation and lung damage were substantially reduced by Tβ4 treatment, as demonstrated by the significant reduction in oedema, total collagen content, lung infiltration by leucocytes, MPO activity in lung homogenates, and histological evidence of the ongoing lung fibrosis. Results of IHC show a strong reactivity for Tβ4 in the lung tissue of Tβ4‐treated mice. Conclusions This is the first report that shows a Tβ4 protective role in lung toxicity associated with BLEO in a mouse model. Future studies are needed to assess its putative antifibrotic properties.